2020
DOI: 10.1038/s41598-020-75269-1
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of epigallocatechin-3-gallate (EGCG) on toxic metalloproteinases-mediated skin damage induced by Scyphozoan jellyfish envenomation

Abstract: Jellyfish stingings are currently raising serious public health concerns around the world. Hence, the search for an effective first aid reagent for the envenomation has been the goal of many investigators in the field. There have been a few previous reports of in vivo as well as in vivo studies suggesting the metalloproteinase activity of scyphozoan jellyfish venom, such as N. nomurai venom (NnV), plays a major role in the pathogenesis. These results have inspired us to develop a metalloproteinase inhibitor as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…EGCG was a well‐known anti‐tumor ingredient which was extracted from green tea (Hwang et al, 2020). Besides, the mechanisms of the anti‐tumor effects (Wei et al, 2020; Zhang et al, 2020), induction of autophagy‐related apoptosis for example (Chen et al, 2020), were well‐studied in many cancers (Kumazoe et al, 2020; Naujokat & McKee, 2020), including bladder cancer (Dettlaff et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…EGCG was a well‐known anti‐tumor ingredient which was extracted from green tea (Hwang et al, 2020). Besides, the mechanisms of the anti‐tumor effects (Wei et al, 2020; Zhang et al, 2020), induction of autophagy‐related apoptosis for example (Chen et al, 2020), were well‐studied in many cancers (Kumazoe et al, 2020; Naujokat & McKee, 2020), including bladder cancer (Dettlaff et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Jellyfish envenomation can induce local consequences such as erythematous eruption, flaring sensations, edema, and necrosis and generate critical systematic symptoms including cardiovascular discomfort, respiratory impairment and hypovolemic attack [ 2 , 3 , 4 , 5 ]. From our prior findings, we have found that most of the scyphozoan jellyfish venoms are rich in metalloproteinase ingredients, which have a vital role in the pathogenesis of damaged skin tissue in an in vivo model [ 23 , 24 ]. The jellyfish Nemopilema nomurai induce life-threatening effects in human beings and cause many deleterious effects [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…PLTX exposure resulted in severe dermatological distress during Ostreopsis blooms; hence PLTX triggers the cytotoxic effects in vitro [ 22 ]. Our former investigation has shown that the metalloproteinase present in the scyphozoan jellyfish venom predominately mediates dermal toxicity [ 23 , 24 ]. However, the mechanism of dermal toxicity involving NnV effects remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…For example, gallocatechin, isoquercitrin, pinostrobin, and quercetin-3-O-rhamnoside extracted from different plant species have been shown to inhibit the hemorrhagic activity of viperid and elapid venoms, as well as some isolated SVMPs [25][26][27][28]. Likewise, EGCG (belongs to the classes of flavonoids) inhibiting Nemopilema nomurai venom metalloproteinases (NnV-MPs) has been demonstrated [29]. The phenolic nuclei of flavonoids possess the ability to interact with proteins through mechanisms such as hydrogen bonding, hydrophobic interactions, metal chelation, and π-π stacking [30].…”
Section: Introductionmentioning
confidence: 99%